2004
DOI: 10.1063/1.1640802
|View full text |Cite
|
Sign up to set email alerts
|

High critical current density and its field dependence in mixed rare earth (Nd,Eu,Gd)Ba2Cu3O7−δ thin films

Abstract: Compared with mono-rare earth 123 films, ternary rare earth (Nd,Eu,Gd)Ba2Cu3O7−δ (NEG123) films show higher critical current density (Jc) and improved irreversibility field (Hirr), but no increase in the characteristic field corresponding to a crossover from a low-field plateau to a linear region in a log Jc–log H plot. At intermediate fields, Jc vs H scales as H(−0.5±0.05) for NEG123, in contrast to H(−0.73±0.05) for mono-rare earth samples such as Gd123. The slow power decay of Jc vs H together with the impr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
29
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 73 publications
(35 citation statements)
references
References 15 publications
5
29
1
Order By: Relevance
“…1 Likewise, REBCO films grown on single-crystal substrates have been reported to have better field dependence of J c than YBCO films. [3][4][5][6] Nevertheless, the difficulty in growing high-J c REBCO films has restricted a possibility for use in coated conductors. Recently, Takahashi et al reported that GdBa 2-Cu 3 O 7-d (GdBCO) films grown on IBAD-Gd 2 Zr 2 O 7 buffer layered metallic substrates had higher selffield J c at 77 K as well as better J c in applied magnetic fields than YBCO films.…”
Section: Introductionmentioning
confidence: 99%
“…1 Likewise, REBCO films grown on single-crystal substrates have been reported to have better field dependence of J c than YBCO films. [3][4][5][6] Nevertheless, the difficulty in growing high-J c REBCO films has restricted a possibility for use in coated conductors. Recently, Takahashi et al reported that GdBa 2-Cu 3 O 7-d (GdBCO) films grown on IBAD-Gd 2 Zr 2 O 7 buffer layered metallic substrates had higher selffield J c at 77 K as well as better J c in applied magnetic fields than YBCO films.…”
Section: Introductionmentioning
confidence: 99%
“…5 Recently, a number of studies have reported the use of nanostructural manipulation to artifically introduce extra pinning sites into YBCO films for enhanced pinning. Examples include multilayering of YBCO with second-phase materials, 6,7 mixed rare-earth doping, 8,9 target compositional modifications either by second-phase BaZrO 3 inclusions 10 or creation of columnar defects comprised of self-aligned BaZrO 3 nanodots and nanorods, 11 process-induced modifications with excess yttrium, 12 and decoration of substrate surfaces by nanoscaled particles. 4,13,14 While all these methods have shown substantial improvements in the angular dependence and in-field J c performance of YBCO films, controlling the number density, morphology, and dimensions of the pinning structures in the superconducting matrix is not straightforward.…”
Section: Introductionmentioning
confidence: 99%
“…Irreversibility fields (B irr ) of the SEG123 film at 77 K were 12.1 T. 12.1 T is higher than that of typical Y123 and Sm123 films. Moreover, this value is higher than 11.8 T of LTG-NEG123 [9] and 9.2 T of PLD-NEG123 [10] films. Therefore, we infer that SEG123 films are effective materials for applications in high magnetic fields.…”
Section: Resultsmentioning
confidence: 85%